2015 10th Computing Colombian Conference (10CCC) 2015
DOI: 10.1109/columbiancc.2015.7333443
|View full text |Cite
|
Sign up to set email alerts
|

Identifying evacuation routes via the P-graph methodology

Abstract: In this work, we propose a method and its concomitant software for the identification and assessment of building-evacuation routes. First, the building floor map is represented via P-graphs, thereby facilitating the identification of the evacuation routes. Second, each route identified is transformed into a time-expanded, process-network synthesis (PNST) problem, which can be algorithmically solved by the P-graph methodology. In the proposed method, each location and passage in the building is defined by a set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Nevertheless, the methodology has been gradually and successfully adapted and deployed for the solution of various design and optimization problems arising in other disciplines. Instances of such problems are the optimal design of supply chains , the routing and scheduling of evacuation schemes in buildings as well as the integration of wastewater systems and energy networks .…”
Section: P‐graph Frameworkmentioning
confidence: 99%
“…Nevertheless, the methodology has been gradually and successfully adapted and deployed for the solution of various design and optimization problems arising in other disciplines. Instances of such problems are the optimal design of supply chains , the routing and scheduling of evacuation schemes in buildings as well as the integration of wastewater systems and energy networks .…”
Section: P‐graph Frameworkmentioning
confidence: 99%
“…Our efforts will be the subject of future contributions in this research area; as well, its application in other domains [2], [15].…”
Section: Discussionmentioning
confidence: 99%
“…Since its inception, it has been shown that the P-graph methodology is suitable for many other areas as well. The P-graph framework is a general network design tool which provides means for generating and analyzing the feasible alternatives of solutions networks, for example, in azeotropic distillation systems, 6 heat-exchanger networks, 7 sustainable energy supply chains, 8 planning evacuation routes, 9 and design sustainable energy networks. 10 However, the extension of the P-graph framework holds further opportunities.…”
Section: Introductionmentioning
confidence: 99%